Non-Hodgkin's lymphoma of the mandible in HIV patient - A Rare Case Report - Mahesh Neerupakam; Jacob Prakash; Sridevi Koduri; Thejasri Vishnubhatla (Contemporary Clinical Dentistry, 2018)
Non-Hodgkin's lymphoma (NHL) is a lymphatic system tumor originating from either B or T lymphocytes and shows a high malignant potential. In HIV-seropositive patients, NHL of head and neck is mainly found in Waldeyer's ring, oral mucosa, salivary glands, paranasal sinuses, and laryngeal tissue. Primary NHL rarely affects the bone. When the lesion affects the bones of the jaws, it is rare in the mandible when compared to the maxilla. In the reported cases, only 0.6% are found in the mandible. NHL of the mandible can be difficult to diagnose, and so the prime aim of the present case report is to establish appropriate diagnosis of one of such kinds. Clinically, they may imitate a dental infection with symptoms of pain and discomfort. A delay in diagnosis may lead to a poor prognosis. Herewith, we present a case of NHL on the lower-right mandible in a 40-year-old male. A correlation of clinical findings, radiological examination, and histopathological examination enabled us in early diagnosis and differentiating it from other similar conditions, thus aiding in initiation of prompt treatment.